ROLE OF HUMAN CAPITAL IN INVESTOR RELATIONS MANAGEMENT: EVIDENCE FROM GERMAN DAX30 COMPANIES - Jäger, Sophia; Au, Cam (PEOPLE: International Journal of Social Sciences, 2020)
Current global trends and discussions in media are mainly focusing on sustainable development goals with an emphasis on the reduction of environmental damages caused by companies. However, another important social/sustainable criterion is constituted by the role of how the company employees are reflected: the human capital. Human capital is defined as the sum of an employee’s experience and skills, which he/she profitably brings into a company. Although being perceived for increasing productivity and thus profitability, the intangible asset is not listed on a company’s balance sheet. In the context of investor relations management, the financial community is more frequently demanding additional (soft) facts on personnel data (e.g. mean age, employee satisfaction, training opportunities) for company valuations. Solely evaluating (hard) facts – such as profits, turnovers, and further classical figures – are no longer adequate to gain the true value of a company. On that basis, we investigate the relevance of human capital within the investor relations management context for all 30 German DAX-companies. In doing so, our research consists of a mixed-methods-approach, thereby combining quantitative and qualitative elements. In the first step, the company reporting – annual reports, personnel reports, CSR-reports, and non-financial reports – for all DAX30-companies is analyzed by using specific criteria model based on the Global Reporting Initiative (GRI). The findings are taken into the qualitative part by interviewing company representatives from DAX30-companies as well as management consulting firms. The overall findings provide empirical evidence, that the German DAX30-companies lack proper strategies to assess personnel data as well as represent proper information for fair company valuations.